1995
DOI: 10.1055/s-2008-1066257
|View full text |Cite
|
Sign up to set email alerts
|

Tethered Spinal Cord: Update of an Analysis of Published Articles

Abstract: Two hundred and fifteen papers written in English between 1943-1994 addressing the issue of tethered spinal cord (TSC) were reviewed using established criteria for research design. Of 127 articles that were not reviews or case reports, 64% specified the diagnostic criteria used for TSC: only 6% discussed the representativeness of the sample. Observer bias was addressed in 6%: reliability in a mere 5%. Only 16% of the 43 articles dealing with clinical trials used a control group: in no case was it randomly chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The arguments for prophylactic untethering are that: (1) a certain (undefined) percentage of these patients will go on to develop symptomatic TCS; (2) one cannot guarantee reversibility of symptoms, even with prompt surgery, and (3) the morbidity for filum sectioning is reasonably low. For these reasons, some authors advocate strongly for prophylactic untethering[ 54, 79, 80], while others remain skeptical[ 37, 81]. Although widely practiced, the beneficial effect of prophylactic untethering in asymptomatic patients remains to be proven by controlled, prospective studies.…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…The arguments for prophylactic untethering are that: (1) a certain (undefined) percentage of these patients will go on to develop symptomatic TCS; (2) one cannot guarantee reversibility of symptoms, even with prompt surgery, and (3) the morbidity for filum sectioning is reasonably low. For these reasons, some authors advocate strongly for prophylactic untethering[ 54, 79, 80], while others remain skeptical[ 37, 81]. Although widely practiced, the beneficial effect of prophylactic untethering in asymptomatic patients remains to be proven by controlled, prospective studies.…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…It is also well established that pre-existing sphincter and motor dysfunction have only a small chance of improving with surgical untethering [6, 10, 11, 12]. Controversy still exists regarding prophylactic surgery and its timing in asymptomatic cases [7, 9, 14, 15]. More recent studies have indicated some effectiveness of prophylactic surgery for spinal lipomas in early childhood [5, 6, 7, 9, 16, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have indicated some effectiveness of prophylactic surgery for spinal lipomas in early childhood [5, 6, 7, 9, 16, 17, 18]. Ethical considerations have precluded randomized prospective study of the efficacy of surgical treatment [14]. …”
Section: Introductionmentioning
confidence: 99%
“…We reviewed 215 papers published between 1943-1994 addressing the issue of tethered spinal cord [Liptak, 1992[Liptak, , 1995. Valid and generalizable conclusions were difficult to draw from these studies because of severe methodological problems.…”
Section: Tethered Spinal Cordmentioning
confidence: 99%